2000
DOI: 10.1086/317142
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Fluctuations in a Babcock‐Leighton Model of the Solar Cycle

Abstract: We investigate the e †ect of stochastic Ñuctuations on a Ñux transport model of the solar cycle based on the Babcock-Leighton mechanism. SpeciÐcally, we make use of our recent Ñux transport model (Dikpati & Charbonneau) to investigate the consequences of introducing large-amplitude stochastic Ñuc-tuations in either or both the meridional Ñow and poloidal source term in the model. Solar cycleÈlike oscillatory behavior persists even for Ñuctuation amplitudes as high as 300%, thus demonstrating the inherent robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
182
3
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(199 citation statements)
references
References 57 publications
12
182
3
2
Order By: Relevance
“…Assuming a sinusoidal behavior with an additional 33% increase in flow velocity at the peak gives an amplitude of about 1.2 m s À1 for the average counterflow at the base of the SCZ toward the equator. Variations in this flow speed from cycle to cycle should be quite large, as judged by the variations seen at 25 in Figure 3, a result consistent with the dynamo modeling of Charbonneau & Dikpati (2000) and Wang et al (2002).…”
Section: Observations Analyses and Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Assuming a sinusoidal behavior with an additional 33% increase in flow velocity at the peak gives an amplitude of about 1.2 m s À1 for the average counterflow at the base of the SCZ toward the equator. Variations in this flow speed from cycle to cycle should be quite large, as judged by the variations seen at 25 in Figure 3, a result consistent with the dynamo modeling of Charbonneau & Dikpati (2000) and Wang et al (2002).…”
Section: Observations Analyses and Resultssupporting
confidence: 79%
“…Fluctuations in the meridional flow (Hathaway 1996), believed to be a product of turbulent convection, have also successfully accounted for variations in the solar cycle that are superposed on the otherwise stable 11 yr periodicity (Charbonneau & Dikpati 2000;Wang et al 2002). From this it has been conjectured that the meridional circulation acts like a solar clock to set the cycle period.…”
Section: Introductionmentioning
confidence: 95%
“…This suggests that if the tilt angles are large, then the next cycle will be short. The fact that the correlation of tilt with the length of the next cycle is significant, but is poor with the strength of the next cycle is consistent with the finding that the length and strength of a cycle are poorly correlated (r c = −0.37, Charbonneau & Dikpati 2000; and r c = −0.35, Solanki et al 2002). Now, tilt angles influence the amount of magnetic flux reaching the poles (Baumann et al 2004) and the polar magnetic flux during activity minimum has been found to be one of the proxies that best predicts the strength of the next cycle (Makarov et al 1989;.…”
Section: Relationships With the Following Cyclesupporting
confidence: 81%
“…In particular, we can expect the time delay due to the advection by the meridional flow (which has a characteristic time-scale of a few solar cycles, see for example Charbonneau & Dikpati 2000) to be much more effective on the behaviour of the dynamo-generated magnetic field. As a consequence, it is mainly the effect of meridional flow which has been tested in previous models (e.g.…”
Section: Discussionmentioning
confidence: 99%